Functional Activity of a Thyroid Nodule under the Influence of Stable Iodide Administration in a Hyperthyroid Patient - Nèmec, J.; Vana, S.; Zamrazil, V.; Rohling, S.; Soumar, J.; Bednár, J. (Nuklearmedizin - NuclearMedicine, 1979)
In a thyrotoxic patient with nodular goiter treated with stable iodide and Carbimazole, a series of 131I scans was performed at different intervals for proposed 131I therapy. Originally, total uptake was suppressed and the node was evaluated as active. The same type of scan was seen repeatedly with uptake increasing for about 6 months following stable iodide withdrawal. Only 9 months later, the effect of l27I disappeared and uptake rose considerably with a reversal of the scan to the picture of a hypofunctioning node. The same distribution was found after therapeutic 131I administration. 6 months following treatment, without any thyrostatic drugs, the patient was euthyroid and on the scan most of tracer was found in the node. It is believed that this change is best explained by the different sensitivity of the nodule and the paranodular tissue to the effect of stable iodide. It is believed that the hyperthyroidism originated in the paranodular tissue highly sensitive on the 127I, while the nodule (presumably an adenoma) was less sensitive and showed uptake only when the paranodular tissue was depressed by l27I or, later, injured by the effect of therapeutic 131I.